Solar-driven alumina calcination for CO2 mitigation and improved product quality. Issue 13 (18th May 2017) - Davis, Dominic; Müller, Fabian; Saw, Woei L.; Steinfeld, Aldo; Nathan, Graham J.
Abstract : Demonstrating technical feasibility and potential for process benefits from alumina calcination with concentrated solar thermal energy. Abstract : We report on the first-of-a-kind experimental demonstration of the calcination of alumina with concentrated solar thermal (CST) radiation at radiative fluxes up to 2190 suns using a 5 kW novel solar transport reactor. Aluminium hydroxide was calcined at nominal reactor temperatures over the range 1160–1550 K to yield chemical conversions of up to 95.8% for nominal residence times of approximately 3 s. Solar energy conversion efficiencies of up to 20.4% were achieved. The mean pore diameter and specific surface area of the solar-generated alumina with the greatest chemical conversion were 5.8 nm and 132.7 m 2 g −1, respectively, which are higher values than are typical for industrial alumina production. In addition, the product is dominated by the γ-phase, which is desirable for the downstream processing to aluminium. This suggests that CST can improve the quality of alumina over existing fossil fuel based processes though a combination of a high heating rate and avoided contamination by combustion products. Furthermore, the solar-driven process has the potential to avoid the discharge of combustion-derived CO2 emissions for the calcination stage of the conventional Bayer process, which is typically 165 kg-CO2 per tonne-alumina.